2020
DOI: 10.1097/md.0000000000019334
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and moxibustion for primary osteoporosis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…However, acupuncture and moxibustion of TCM repair inflammatory damage in RA through thermal conduction and mechanical stimulation of acupoints [21]. On the other hand, acupuncture is shown to interfere with cholinergic nerve function at the central level and affects the release of glucocorticoid receptors and melatonin, thus effectively repairing tissue inflammatory injury [22]. Alonso et al found enhanced release levels of preproopiomelanocortin and preprodynorphin in the hypothalamus of mice by acupuncture; preproopiomelanocortin and preprodynorphin have positive effects on anti-inflammatory pain and a strengthening analgesic effect in the human body [23], which also explained the excellent effect of acupuncture and moxibustion of TCM on relieving RA pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, acupuncture and moxibustion of TCM repair inflammatory damage in RA through thermal conduction and mechanical stimulation of acupoints [21]. On the other hand, acupuncture is shown to interfere with cholinergic nerve function at the central level and affects the release of glucocorticoid receptors and melatonin, thus effectively repairing tissue inflammatory injury [22]. Alonso et al found enhanced release levels of preproopiomelanocortin and preprodynorphin in the hypothalamus of mice by acupuncture; preproopiomelanocortin and preprodynorphin have positive effects on anti-inflammatory pain and a strengthening analgesic effect in the human body [23], which also explained the excellent effect of acupuncture and moxibustion of TCM on relieving RA pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moxibustion, as a commonly used traditional Chinese medicine therapy, has a wide range of adaptation, clinical indications in all branches, and is simple, easy to learn, and timely. Moxibustion therapy is not only used in hospitals but also can be used in families for self-therapy and mutual therapy, which is attached to the medical viewpoint of "early treatment is the most important" of Traditional Chinese medicine [6][7][8]. Moxibustion combines the properties of moxa leaves to promote the flow of Qi blood, warm the middle, and expel cold with the warm stimulation of moxibustion fire, which has the effect of warming the meridians, promoting the movement of Qi blood and the transportation of water and fluids [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Application of acupuncture in the treatment of osteoporosis was described in Huangdi Neijing, the ancient classical text of acupuncture. In recent years, many studies have investigated the efficacy of acupuncture for the treatment of primary osteoporosis in clinical practice, and the findings have shown that acupuncture is effective in improving osteoporosis (17)(18)(19)(20). Moreover, a previous study on secondary osteoporosis in patients with spinal cord injuries has reported an increase in BMD after 3 months of adjunctive acupuncture treatment, but the difference is not statistically significant (21).…”
Section: Introductionmentioning
confidence: 99%